2004
DOI: 10.1021/ma035456q
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Thermosetting Poly(imide−ester):  Synthesis and Properties

Abstract: A new family of polymer, namely hyperbranched thermosetting poly(imide−ester) (HBPIE), was successfully prepared by the esterification reaction between a hyperbranched oligoimide terminated with carboxylic end groups (−COOH) and a hyperbranched oligoester terminated with acetoxy end groups (−OAc). The hyperbranched oligoimide has a degree of branching of one, M w = 14 180, and polydispersity Pd = 1.953. The −OAc-terminated oligoester has M w = 7000 and polydispersity Pd = 1.17. The NMP solution of the oligoimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
0
20
2
Order By: Relevance
“…The model, which assumes that dendritic macromolecules are very rigid with not backfolding of the molecular arms, is supported by the molecular modeling experiments of Naylor et al 7 However, if inward folding is allowed, the kinetic model of Lescanec and Muthukumar 8 predicts that the chain ends are buried at all regions of dendritic macromolecules. Other studies dealing with the dielectric properties of hyperbranched thermosetting poly͑imide-ester͒ 20 and hyperbaranched aromatic polyamide and polyamide-6,6 blends 21 have also been reported. Monte Carlo simulations based on equilibrium structures carried out by Mansfield and Klushin 9 support the structures predicted by the Lescanes and Muthukumar model.…”
Section: Introductionmentioning
confidence: 99%
“…The model, which assumes that dendritic macromolecules are very rigid with not backfolding of the molecular arms, is supported by the molecular modeling experiments of Naylor et al 7 However, if inward folding is allowed, the kinetic model of Lescanec and Muthukumar 8 predicts that the chain ends are buried at all regions of dendritic macromolecules. Other studies dealing with the dielectric properties of hyperbranched thermosetting poly͑imide-ester͒ 20 and hyperbaranched aromatic polyamide and polyamide-6,6 blends 21 have also been reported. Monte Carlo simulations based on equilibrium structures carried out by Mansfield and Klushin 9 support the structures predicted by the Lescanes and Muthukumar model.…”
Section: Introductionmentioning
confidence: 99%
“…However, compression significantly reduces the broad distribution of relaxation times which is an indication that pressure induces dynamic homogeneity in this dendritic material. Xu and Economy [12] reported the synthesis and dielectric properties of thin films of hyperbranched thermosetting poly(imide-ester). Hakme et al [13] recently reported dielectric spectroscopy of hyperbranched aromatic polyamide and polyamide-6,6 blends, where the authors found three relaxations: two secondary relaxations, and one primary a relaxation in the hyperbranched polymers as well as in the blends.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 1 , CPO1 , DMTMM , and Xu‐COOH were prepared according to the methods described in the literature. Chemicals were purchased from Acros France supplier or Aldrich France supplier and used as received.…”
Section: Experimental Partmentioning
confidence: 99%
“…Toward this goal, we selected the CPO1 chromophore because it displays a very high quadratic hyperpolarizability coefficient ( μβ = 31,000 ⋅ 10 −48 esu at 1990 nm) and can be readily synthesized in multigram scale (Fig. ) . This push–pull type chromophore (D‐π‐A) is composed of an indoline donor group (D) coupled to a TCF (2‐dicyanomethylidene‐3‐cyano‐4,5,5‐trimethyl‐2,5‐dihydrofuran) (A) through a ring‐locking polyene (π).…”
Section: Introductionmentioning
confidence: 99%